Identification of Psychological Training Strategies Essential for Volleyball Performance - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
This chapter highlights the contribution of certain training psychological strategic elements in the prediction of players performance during the indoor volleyball tournament. It has been demonstrated from the study findings that training strategic variables that included attentional control, imagery, relaxation, activation, goal setting, emotional control, automaticity as well as self-talk are found to be non-trivial in predicting the performance of the elite volleyball players. It has also been demonstrated from the current finding that linear-based SVR is able to yield an accurate prediction of the performance of the players. It is then inferred that the ability of an athlete to develop a personal strategy for dealing with adversity could to a larger extend assist the athlete in delivering good performance during competition in this sport. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.